MERENCANAKAN DAN MENGKOORDINASIKAN KOMUNIKASI PEMASARAN TERINTEGRASI - Nurati, Dian Esti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2009)
ABSTRACT Modern marketing procedures need to develop a good product, with the offer price, interesting and easily obtained by making the target customer. Companies need to make communication with our customers who have current and potential customers the parties have interests in the company and the general public. Each company can not pull out of his role as promoter and communicator. For most companies, the question is not whether to make the communication or not, but more on what will be communicated, to how much the frequency of communication. Mixture marketing communications of advertising, sales promotion, public relation and publicity, sales in private, and whose direct marketing mail, telephone, facsimile, e-mail communicator, and other non-personal. Keywords: marketing communication, marketing communications, customers.